Progesterona de longa ação na indução da ciclicidade e sincronização do ciclo estral em ovelhas - D'Ávila, Camila Amaral (2023)
The use of reproductive biotechniques and hormonal protocols allow the manipulation of the estrous cycle in sheep, which is interesting since this species is seasonally polyestrous. In this sense, progesterone (P4) intravaginal devices (IVD) are widely used to induce cyclicity and synchronization of the estrous cycle. The search for alternatives, with lower cost and less environmental impact is necessary. In sheep there are few studies on the use of injectable progesterone (iP4), specially on long acting (LA) iP4. Thus, the aim of this study was to evaluate the effects of LA iP4 on estrus induction in ewes outside the breeding season. In experiment 1, to evaluate the serum concentration of P4, 39 ewes were allocated into three groups: control (n = 14); 37.5 mg iP4 im (iP4 37.5, n = 13) and 75 mg iP4 im (iP4 75, n = 12). P4 dosing in a subset of animals (5 per group) showed the highest P4 level at 48 h and reduction to baseline levels 10 days after injection, when all females received an IVD containing 60 mg of medroxyprogesterone acetate (MPA) which remained for 11 days. At withdrawal, the animals received 400 IU of equine chorionic gonadotropin (eCG) intramuscularly (im), and the rams remained with the ewes for three days. On days 6 and 12 after estrus, blood samples were collected from a subset (n = 5 per group) of ewes. The iP4 75 group had lower luteal P4 concentration and a lower conception rate (35 days after mating) when compared to the other groups. In experiment 2, to test the replacement of IVD by iP4, 36 ewes were distributed into two treatments: control (n = 10), IVD for nine days and 300 IU of eCG at removal; and iP4 75 (n = 26), in which the animals received 75 mg of iP4 im and, after 9 (n = 13) or 10 (n = 13) days, received 300 IU of eCG. Estrus onset and conception rates were lower in iP4-treated groups. Eleven days after estrus, a subset of animals (5 from the control and 10 from the iP4 75) had P4 concentrations above 1 ng/mL, indicating ovulation. Collectively, it is concluded that the application of 75 mg of long-acting iP4 maintained levels above 1 ng/mL for at least 7 days and negatively affected luteal P4 concentration and conception rate after a subsequent cyclicity induction protocol. Treatment with 75 mg of iP4 associated with eCG is adequate to induce ovulation, but it inhibits the manifestation of estrus. Therefore, the use of iP4 is not recommended until further studies are carried out to evaluate new doses and times of administration.